Optimization in active vibration control: virtual experimentation using COMSOL multiphysics - MATLAB integration - Md Nor, Khairul Affendy; Abdul Muthalif, Asan Gani; Wahid, Azni N. (The Institute of Electrical and Electronics Engineers, 2014)
This paper demonstrates optimization of collocated sensor-actuator location and the controller gains of active vibration control system. Ant colony optimization algorithm is employed for this purpose. Instead of using equation-based modeling for the system, the plant is a finite element model developed in COMSOL Multiphysics software, which later interfaced with the MATLAB-coded optimization algorithm using the Livelink for MATLAB feature. The benchmark model is a simply supported thin plate excited and attenuated by two piezoelectric patches. The optimization is based on the average energy reduction across a frequency range between 11 Hz to 50 Hz, which covers the first three modes. It is found that the maximum attenuation achieved is 68.31% using optimal values of sensor-actuator location and controller gains.